What drives foreign direct investment in the tradable sector? - Mateus, Márcio (2017)
Researchers usually investigate the determinants of aggregated Foreign Direct Investment (FDI), although there is evidence that the sectoral distribution of FDI matters and that too much FDI in the non-tradable sector can exacerbate external imbalances. This paper differs from most existing studies on FDI determinants by focusing on tradable sector FDI. We show that countries with a large market size, a higher degree of economic openness, a higher productivity level and good institutions are more likely to receive FDI in the tradable sector. We also show that physical distance does not represent so large an obstacle for tradable sector FDI, as it seems to represent for aggregated FDI. In contrast, based on results of empirical studies on aggregated FDI which share a common border, it does not seem to have an impact on the attraction of FDI for the tradable sector. This paper uses a modified gravity model to compare different methods, specifications and variables, in order to obtain robust results.